Customers’ awareness and intention to purchase towards green marketing programs in restaurants / Tajul Fitri Mohd Diah - Mohd Diah, Tajul Fitri (2010)
The time has come for Malaysia to seriously "go green". Even though the government started the efforts of organizing energy efficiency and renewable energy awareness programs since the year 2000, the awareness of the public towards environmental issues, in general, is still lacking. Not all customers really concern on and highly involve in environmental issues. This situation seemed to have affected their intention to exercise their green purchase. Customers are not quite as environmentally friendly as they would like to think they are. A research showed even customers who consider, themselves, to be very "green" are not always willing to cut down their impact on the environment (Anonymous, 2007). Therefore, the customers’ awareness and purchase intention towards restaurant green marketing programs in relation to the customers’ characteristics was studied. This study aimed to satisfy the following objectives: (1) to identify the significant difference between customers’ characteristics on customers’ green awareness on go green program and customers’ purchase intention towards go green program; (2) to investigate the relationship between customers’ green awareness on go green program with customers’ purchase intention towards restaurant green marketing programs; (3) and, to determine the most influential restaurant green marketing program. This descriptive cross-sectional study utilized quantitative method of data collection. A self-administrated, closed- and open ended questionnaire was used to survey a sample of customers patronizing the selected franchised fast food restaurants for this research. Findings showed, firstly, the customers with tertiary level education have higher green awareness and green purchase intention. Secondly, females are more aware toward go green programs and they also have more intention to purchase at a restaurant green marketing program compared with males. Thirdly, it was found that customers with green awareness have the intention to purchase in restaurants with green marketing programs. Lastly, the waste management program was rated as the most influential green marketing program for restaurant business by majority (46%) of the respondents in motivating their purchase intention.